The effects of elicitors and precursor on in vitro cultures of Sauropus androgynus for sustainable metabolite production and antioxidant capacity improvement - Wee, Sin Ling (2015)
Sauropus androgynus, commonly known as ‘sweet shoot’ is an underutilized crop known for its high nutritive values and medicinal properties. To date, scientific studies assessing the potentially important benefits of sweet shoot for use as medicinal plants are still limited, with only six studies reporting on in vitro propagation and nine articles describing the production of secondary metabolites. The present study revealed that shadehouse-grown plants contained a low yield of bioactive phytochemicals, such as phenolic (61.20 µg/10g FW), flavonoid (193.62 µg/10g FW), naringenin (128.01 µg/10g FW), quercetin (1.56 µg/10g FW) and kaempferol (274.85 µg/10g FW). Moreover, it also had very low antioxidant activity in DPPH (54.03%) and FRAP (397.56 µg/10g FW) assay. The elicitation of cultured tissues is therefore necessary to improve the production of phytochemical compounds and to increase the antioxidant capacity in sweet shoot. In this study, four different types of cultured tissues (in vitro shoot cultures, light-induced callus, dark-induced callus and somatic embryos) were selected to achieve this goal, followed by the extraction of phytochemicals from these cultured tissues treated with elicitors and precursor for better production of phytochemicals.